Structure activity relationship of the binding of p-coumaroyl glucose to glycogen phosphorylase and its effect on hepatic cell metabolic pathways - Anastasia S. Tsagkarakou; Styliani A. Chasapi; Symeon M. Koulas; Ioannis Tsialtas; Efthimios Kyriakis; Christina E. Drakou; Sándor Kun; László Somsák; Georgios A. Spyroulias; Anna-Maria G. Psarra; Demetres D. Leonidas (Elsevier, 2021)
The binding of p-coumaroyl glucose to glycogen phosphorylase (GP; a pharmaceutical target for the development of antihyperglycaemic drugs) has been studied by kinetics, and X-ray crystallography while its effect to HepG2 cells metabolism has been assessed by NMR metabolomics. p-Coumaroyl glucose is a potent inhibitor of human liver GP with a Ki value of 213 μΜ that binds at the active site of the enzyme. Comparative structural analysis with chemically similar GP inhibitors reveals the structural basis of its inhibitory potency. NMR metabolomics analysis revealed that HepG2 cells in the presence of p-coumaroyl glucose actively response to higher glucose uptake from their environment and a display an "insulin-sensitizing'' state. Furthermore, NMR metabolomics analysis indicates an enhancement of gluconeogenesis towards lipid metabolism and glycerol-derived components.